Induction of HCO(3)(−) Transporting Capability and High Photosynthetic Affinity to Inorganic Carbon by Low Concentration of CO(2) in Anabaena variabilis - Marcus, Yenda (1982)
The apparent affinity of photosynthesis for inorganic carbon in Anabaena variabilis strain M-3 increased during the course of adaptation from high to low CO(2) concentration (5% and 0.03% v/v CO(2) in air, respectively). This was attributed to an increased ability of the cells to accumulate inorganic carbon during the course of adaptation to low CO(2) conditions. The release of phycobiliproteins was used to evaluate the sensitivity of the cells to lysozyme treatment followed by osmotic shock. High CO(2)-grown cells were more sensitive to this treatment than were low CO(2) ones. The efflux of inorganic carbon from cells preloaded with radioactive bicarbonate is faster in high than it is in low CO(2)-adapted cells. It is postulated that the cell wall or membrane components undergo changes during the course of adaptation to low CO(2) conditions. This is supported by electron micrographs showing differences in the cell wall appearance between high and low CO(2)-grown cells. The increasing ability to accumulate HCO(3)(−) and the lessened sensitivity to lysozyme during adaptation to low CO(2) conditions depends on protein synthesis. The increase in affinity for inorganic carbon during the adaptation to low CO(2) conditions is severely inhibited by the presence of spectinomycin. Incubation in the light significantly lessens the time required for the adaptation to low CO(2) conditions.